Assessing deviations for HPCs obtained during COVID‐19 (ADHOC): Evaluating impact of the COVID‐19 pandemic on cellular therapy products and processes, the BEST collaborative study. Issue 4 (16th March 2023) - Thibodeaux, Suzanne R.; Coble, Dean; Day, Victoria; Fontaine, Magali J.; Gabelli, Maria; Gardiner, Nicola; Geach, Tamara; Schwartz, Joseph; Vasovic, Ljiljana V.; Wyre, Rachael; Girdlestone, John
Abstract: Background: The success of allogeneic hematopoietic stem cell transplantation is dependent on a world‐wide network of collection centers providing donations that predominantly have been infused as fresh cells. The logistics chain that supports the just‐in‐time delivery model for stem cell and immunotherapy products was severely stressed by the COVID pandemic, and in early 2020 a number of national and international bodies recommended that cells should be cryopreserved at the collection or transplant center to avoid interruptions in their acquisition or delivery to patients who had started conditioning. Study Design: To assess the potential consequences of such pandemic‐related deviations to normal practice, we surveyed nine international laboratories to determine if the characteristics or transplant outcomes of allogeneic stem cell donations differed in the immediate periods before and after the switch to routine cryopreservation. Results: Nine centers on two continents provided data for 72 HSC donations just before, and 71 just after, switching to cryopreservation for allogeneic HSC products. No statistically significant differences between the period before and after cryopreservation were noted for time from product collection to receipt, product temperature at receipt, or CD34 + cell viability at receipt. There was an indication of slower absolute neutrophil count recovery after cryopreservation was required (mean time of 15 vs. 17.6 days). Discussion: While there were no apparent changes to most parameters studied, there was an indication of slower neutrophil engraftment that will need to be examined in larger, longer term studies.